Improved tribocorrosion performance of bio-functionalized TiO2 nanotubes under two-cycle sliding actions in artificial saliva - Alves, Sofia A. [UNESP]; Rossi, André L.; Ribeiro, Ana R. [UNESP]; Toptan, Fatih; Pinto, Ana M.; Shokuhfar, Tolou; Celis, Jean-Pierre; Rocha, Luís A. [UNESP] (Elsevier, 2018)
After insertion into bone, dental implants may be subjected to tribocorrosive conditions resulting in the release of metallic ions and solid wear debris, which can induce to peri-implant inflammatory reactions accompanied by bone loss, and ultimately implant loosening. Despite the promising ability of TiO2 nanotubes (NTs) to improve osseointegration and avoid infection-related failures, the understanding of their degradation under the simultaneous action of wear and corrosion (tribocorrosion) is still very limited. This study aims, for the first time, to study the tribocorrosion behavior of bio-functionalized TiO2 NTs submitted to two-cycle sliding actions, and compare it with conventional TiO2 NTs. TiO2 NTs grown by anodization were doped with bioactive elements, namely calcium (Ca), phosphorous (P), and zinc (Zn), through reverse polarization anodization treatments. Characterization techniques such as scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and scanning transmission electron microscopy (STEM), were used to characterize the films. Tribocorrosion tests were carried out in artificial saliva (AS) by applying two cycles of reciprocating sliding actions. The open circuit potential (OCP) was monitored before, during, and after both cycles of sliding, during which the coefficient of friction (COF) was calculated. The resulting wear scars were analyzed by SEM and EDS, and wear volume measurements were performed by 2D profilometry. Finally, the mechanical features of TiO2 NTs were accessed by nanoindentation. The results show that bio-functionalized TiO2 NTs display an enhanced tribocorrosion performance, ascribed to the growth of a nano-thick oxide film at Ti/TiO2 NTs interface, which significantly increased their adhesion strength to the substrate and consequently their hardness. Furthermore, it was discovered that during tribo-electrochemical solicitations, the formation of a P-rich tribofilm takes place, which grants both electrochemical protection and resistance to mechanical wear. This study provides fundamental and new insights for the development of multifunctional TiO2 NTs with long-term biomechanical stability and improved clinical outcomes.
Keywords: Bio-functionalization; Mechanical properties; TiO2 nanotubes; Tribocorrosion; Two-cycle-sliding